Revisting the role of institutional and political factors on economic integration. The case of Latin America - Florensa, Luis Marcelo (2014)
Fil: Florensa, Luis Marcelo. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Instituto de Economía y Finanzas; Argentina.